Does the Leverage Ratio Mediate the Effect of Liquidity Ratios, Profitability Ratios, and Activity Ratios on Stock Prices? (Empirical Study of Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange for the Period of 2015-2019) - Rudolf Lumbantobing; Susanto Salim (Enrichment : Journal of Management, 2021)
This research explores the mediating effect of solvency ratios on the effect of liquidity ratios, profitability ratios and activity ratios on the prices of shares of food and beverage sub-sectors listed on the Indonesia Stock Exchange in 2015-2019. The data of this study were obtained from 10 food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2015-2019 which were used as research samples. The data was obtained by the purpose sampling method with the provisions of the food and beverage sub-sector company that issued an annual report for five years in a row namely 2015 to 2019, included a complete financial ratio in each annual report, and included a report on share prices in the period. The findings of this study showed that The solvency ratio significantly mediates the positive effect of the liquidity ratio on stock prices. The solvency ratio mediates the negative effect of the activity ratio on stock prices. The negative effect of the activity ratio on stock prices will be even more negative when the solvency ratio increases. This findings suggested that to increase the stock price of companies that have high liquidity ratios should be done when the company's debt ratio decreases. And for companies that have high profitability and high asset turnover, to increase their share price by reducing their debt ratio.